Q: What is 5x minus (negative 3x)?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

5x² - 18x + 9 = (5x² - 15x) - (3x - 9) = 5x(x - 3) - 3(x - 3) = (5x - 3)(x - 3).

The discriminant b2-4ac is -23

6-3x = 5x-10x+10 6-3x = -5x+10 -3x+5x = 10-6 2x = 4 x = 2

(2x + 5) + (5x - 6) + (-4x + 2) = 3x + 1 There are three items so average = (3x + 1)/3 = x + 1/3

That will depend on the plus or minus values of the given terms which have not been given

Related questions

3x - 5x + x = -x

5x - 2x = 3x

5x

2x minus 3x is equal to -x.

3x+4 = 5x-6 3x-5x = -6-4 -2x = -10 x = 5

3x + 7 = 5x + 13 3x - 5x = 13 - 7 -2x = 6 -x = 3 x = -3

3x2 - 5x2 = -2x2

3x + 9 = 5x - 43x +13 = 5x13 = 2x13/2 = xso x = 6.5

6x2 + 5x - 6 is factored out to (2x + 3)(3x - 2).

That depends on the plus or minus values 0f 8, 5x and 7 which have not been given

5x3 - 3x2 + 2x = x*(5x2 - 3x + 2) The quadratic has no real factors.

5x² - 18x + 9 = (5x² - 15x) - (3x - 9) = 5x(x - 3) - 3(x - 3) = (5x - 3)(x - 3).